Innovative Learning in Modern Boarding School: Evaluating Effectiveness and Embedded Character Values at PPM Surya Buana Malang - Afifah Maharani; Andyni loisalina hidayat; Nadlirotul Maulida (UIN Siber Syekh Nurjati Cirebon, 2025)
Abstrak :The learning model in modern Islamic boarding schools is a strategic issue to study because the education system implemented is not only directed at achieving academic competencies, but also at strengthening the character, discipline, and religious values of students. As an Islamic boarding school, PPM Surya Buana Malang applies an integrated learning pattern between intracurricular activities, co-curricular activities, and the daily lives of students so that the learning process takes place comprehensively. This study aims to analyze the concept and practice of the learning model developed at PPM Surya Buana by examining three main focuses: (1) integration of Islamic boarding school curriculum, (2) patterns of internalization of character values through the Islamic boarding school system, and (3) the level of effectiveness of the learning model on the formation of student character. This study uses a qualitative approach through three data collection techniques, namely literature study, direct observation in the Islamic boarding school environment, and interviews with managers and educators at PPM Surya Buana. Data were collected through literature review and analyzed using a thematic model to find the dominant conceptual pattern. The results of the study indicate that: (1) the Islamic boarding school curriculum is integrated in learning through strengthening Islamic material, habituating worship, and activities that support student discipline; (2) internalization of character values is built through role models, intensive mentoring, and 24-hour supervision; and (3) the effectiveness of character formation is proven to be high because students undergo a consistent learning process both in class and in the dormitory environment. These findings indicate that the learning model at PPM Surya Buana Malang contributes greatly to producing students with strong characters and who are ready to adapt to the demands of the modern era.Keywords : Learning models, Islamic boarding school curriculum, character values.Abstrak :Model pembelajaran di pondok pesantren modern menjadi isu strategis untuk dikaji karena sistem pendidikan yang diterapkan tidak hanya diarahkan pada pencapaian kompetensi akademik, tetapi juga pada penguatan karakter, kedisiplinan, serta nilai-nilai keagamaan santri. Sebagai lembaga pendidikan berasrama, PPM Surya Buana Malang menerapkan pola pembelajaran yang terintegrasi antara kegiatan intrakurikuler, kokurikuler, dan kehidupan harian santri sehingga proses belajar berlangsung secara komprehensif. Penelitian ini bertujuan menganalisis konsep dan praktik model pembelajaran yang dikembangkan di PPM Surya Buana dengan meninjau tiga fokus utama: (1) pengintegrasian kurikulum pesantren, (2) pola internalisasi nilai karakter melalui sistem kehidupan berasrama, dan (3) tingkat efektivitas model pembelajaran terhadap pembentukan karakter santri. Penelitian ini menggunakan pendekatan kualitatif melalui tiga teknik pengumpulan data, yaitu studi literatur, observasi langsung di lingkungan pesantren, dan wawancara dengan pihak pengelola serta pendidik di PPM Surya Buana. Data dikumpulkan melalui teaah pustaka dan dianalisis dengan model tematik untuk menemukan pola konteks yang dominan. Hasil penelitian menunjukkan bahwa: (1) kurikulum pesantren disertakan ke dalam pembelajaran melalui penguatan materi keislaman, pembiasaan ibadah, serta kegiatan yang mendukung kedisiplinan santri; (2) internalisasi nilai karakter dibangun melalui keteladanan, pendampingan intensif, dan pengawasan selama 24 jam; dan (3) efektivitas pembentukan karakter terbukti tinggi karena santri menjalani proses belajar yang konsisten baik di ruang kelas maupun di lingkungan asrama. Temuan ini menunjukkan bahwa model pembelajaran di PPM Surya Buana Malang memberikan kontribusi besar dalam mencetak santri yang berkarakter kuat dan siap beradaptasi dengan tuntutan era modern.Kata Kunci: Model pembelajaran, kurikulum pesantren, nilai karakter.